(untitled) (Scientific journal of the Fergana State University, 2024)
Abstract The article discusses the types, useful properties and technology of growing Sansevieria trifasciata in our region, as an ornamental plant, which the center of origin is tropical and subtropical areas. This plant is used in medicine, when creating a phytodesign, landscaping of premises. The culture attracts flower growers with its erect leathery leaves with unusual patterns. The main useful property of the plant is to ensure the quality and purity of atmospheric air in the room. The purpose of the study. The bioecological features of sansevieria are the development of reproduction technology in the conditions of our region, the study of fertilizer application standards. The study was conducted on Sansevieria trifasciata using the method of vegetative reproduction experimentally.